Health economic evaluation of an internet intervention for depression (deprexis), a randomized controlled trial - Viola Gräfe; Steffen Moritz; Wolfgang Greiner (Health Economics Review, 2020)
Background: Depressive disorders often remain undiagnosed or are treated inadequately. Online-based programs may reduce the present treatment gap for depressive disorders and reduce disease-related costs. This study aimed to examine the potential of the internet intervention "deprexis" to reduce the total costs of statutory health insurance. Changes in depression severity, health-related quality of life and impairment in functioning were also examined. Method: A total of 3805 participants with, at minimum, mild depressive symptoms were randomized to either a 12- week online intervention (deprexis) or a control condition. The primary outcome measure was statutory health insurance costs, estimated using health insurers' administrative data. Secondary outcomes were: depression severity, health-related quality of life, and impairment in functioning; assessed on patient's self-report at baseline, posttreatment, and three-months' and nine-months' follow-up. Results: In both groups, total costs of statutory health insurance decreased during the study period, but changes from baseline differed significantly. In the intervention group total costs decreased by 32% from 3139 exteuro per year at baseline to 2119 exteuro in the study year (vs. a mean reduction in total costs of 13% in the control group). In comparison to the control group, the intervention group also showed a significantly greater reduction in depression severity, and impairment in functioning and a significantly greater increase in health-related quality of life. Conclusion: The study underlines the potential of innovative internet intervention programs in treating depressive disorders. The results suggest that the use of deprexis over a period of 12 weeks leads to a significant improvement in symptoms with a simultaneous reduction in the costs of statutory health insurance.
Keywords: 330; Economic issues; Outcome studies; Health economic evaluation; E-mental-health; Deprexis; Depression; Randomized controlled trial